2019
DOI: 10.5713/ajas.18.0473
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of microRNAs in skeletal muscle of sheep by deep sequencing

Abstract: Objective MicroRNAs are a class of endogenous small regulatory RNAs that regulate cell proliferation, differentiation and apoptosis. Recent studies on miRNAs are mainly focused on mice, human and pig. However, the studies on miRNAs in skeletal muscle of sheep are not comprehensive. Methods RNA-seq technology was used to perform genomic analysis of miRNAs in prenatal and postnatal skeletal muscle of sheep. Targeted genes were predicted using miRanda software and miRNA-mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…With the development of sequencing technology, it is found that miRNAs in animal transcriptomes are more abundant than previously thought. There are now thousands of such molecules in skeletal muscles of many species, such as humans (Horak et al, 2016), sheep (Liu et al, 2019), and goat (Guo et al, 2016). Horak et al (2016) reviewed several representative miRNAs found in basic research and sequencing that were specifically expressed in skeletal muscle and played an important role in proliferation, differentiation, and regeneration, including miR-1, miR-133a, miR-133b, miR-206, miR-208b, miR-486, and miR-499.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of sequencing technology, it is found that miRNAs in animal transcriptomes are more abundant than previously thought. There are now thousands of such molecules in skeletal muscles of many species, such as humans (Horak et al, 2016), sheep (Liu et al, 2019), and goat (Guo et al, 2016). Horak et al (2016) reviewed several representative miRNAs found in basic research and sequencing that were specifically expressed in skeletal muscle and played an important role in proliferation, differentiation, and regeneration, including miR-1, miR-133a, miR-133b, miR-206, miR-208b, miR-486, and miR-499.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs are DEmiRNAs in this study. Liu et al (2019) analyzed the GO and KEGG enrichment terms for the 345 DEmiRNAs of sheep's longissimus dorsi between fetuses and adults and showed the regulatory network of 29 DEmiRNAs and 298 target genes. In addition, Wang et al (2014) revealed the expression profiles of goat miRNAs in the fetal and 6-month-old stages, identified 336 DEmiRNAs, and found that miR-424-5p and miR-29a may regulate muscle development.…”
Section: Discussionmentioning
confidence: 99%
“…Myomirs, oar-miR-1 and oar-miR-206 were over-expressed while oar-miR-133b and oar-miR-486 showed lower expression in Bandur sheep. Table 2 lists the miRNAs differentially expressed in Bandur that are known to be associated with muscle growth and development in sheep 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of miRNAs in skeletal muscles of various livestock species provides the possibility of identifying key regulators of muscle traits that can be used as biomarkers 21,31 . Several studies have identified and profiled miRNAs in the skeletal muscles of sheep 11,12 . However, there is dearth of information on molecular regulators for meat type sheep in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation